PENGARUH PENGARUH KUALITAS PRODUK, BRAND IMAGE, DAN INFLUENCER TERHADAP KEPUTUSAN PEMBELIAN BEDAK GARNIER DI KOTA BATAM - Yulianti, Bella; Nainggolan, Nora Pitri (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2025)
Beauty products have become an important part of the lifestyle of most people, especially those who live in big cities like Batam City. Cosmetics such as pressed powder have become an important necessity for daily care and improving appearance. The aim of this research is to describe the influence of product quality, brand image and influencers on purchasing decisions for Garnier powder in Batam City. This research involved a sample of 100 participants selected based on certain criteria, including individuals who purchased Garnier powder in Batam City. Data was collected through questionnaires distributed to these consumers. This research uses descriptive techniques based on a quantitative approach. Various statistical tests were carried out using SPSS version 27. The research results can show that the product quality variable (X1) is 11,844 > from the t table of 1,984, with a significance value of 0.00 < 0.05, the brand image variable (X2) is 17,357 > than t table is 1,984, with a significance value of 0.00 < 0.05, and the influencer variable (X3) is 15,871 > from the t table of 1,984, with a significance value of 0.00 < 0.05. Product quality, brand image and influencers have a significant influence on purchasing decisions as shown by the calculated f value of 123,743 > from the t table of 2.70 while the significance value is 0.00 < 0.05. The R2 value is 79.5% and the remaining 20.5% is influenced by variables not included in this research. Keywords: Product Quality, Brand Image and Influencers, Purchase Decisions